Journalisme immersif et empathie : l’émotion comme connaissance immédiate du réel - Céline Ferjoux; Émilie Ropert Dupont (Communiquer)
This article questions the frequent use of the notions of immersion and empathy in discourses relating to immersive journalism between 2014 and 2019. The euphoria expressed about the virtual reality capabilities to transcribe the accuracy of the facts can be understood at different levels.  It symbolises a technological utopianism. It also illustrates the paradigm of socio-technical diffusion specific to innovations. It finally reformulates a dialectical ambivalence of the journalism’s ethos, where emotion appears to be both a source of motivation and a raw material for information.